Analisis Pengaruh Current Ratio, DER, TATO dan EBITDA Terhadap Kondisi Financial Distress Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Oktariyani, Amanda (Akuntansi dan Manajemen, 2019)
This study aims to determine whether the financial ratios that proxied by Current Ratio, Debt to Equity Ratio, Total Asset Turnover, and Earning Before Interest, tax, Depreciation, and Amortization affect to Financial distress in manufacturing companies listed on the IDX from 2013 to 2017. The samples consist of 46 manufacturing companies. The data analysis method used is logistic regression analysis. The results showed that Total Asset Turnover and Earning Before Interest, Tax, Depreciation and Amortization influence partially to Financial Distress. Whereas, Current Ratio and Debt to Equity Ratio has not influence partially to Financial distress. The results showed that Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and Earning Before Interest, Tax, Depreciation and Amortization (EBITDA) influence simultaneously to Financial Distress on manufacturing companies listed on Indonesia Stock Exchange (IDX) 2013-2017.